Maintenance ECT in schizophrenia: A systematic review. (June 2018) - Ward, Heather Burrell; Szabo, Steven T.; Rakesh, Gopalkumar
Highlights: There is currently limited evidence to justify clinical use of M-ECT in schizophrenia. The majority of patients with schizophrenia who receive M- ECT improve. M-ECT could provide an effective form of relapse prevention for schizophrenia. Persistent cognitive side effects are minimal for M-ECT in schizophrenia. Abstract: Relapse after discontinuation of ECT is significant in patients with schizophrenia. The purpose of this systematic review was to examine use of M-ECT in schizophrenia to guide clinical decision making for relapse prevention in schizophrenia. We reviewed studies examining the role of continuation (C-ECT) and maintenance electroconvulsive therapy (M-ECT) in schizophrenia. Following PRISMA guidelines, we included randomized controlled trials, open label trials, retrospective chart reviews, case reports, and case series in this review. We evaluated adjunctive pharmacological regimens; ECT treatment parameters, including frequency, duration of continued treatment, electrode placement; clinical outcomes including cognitive side effects and relapse rates from included studies. Our findings suggest M-ECT could provide an effective form of relapse prevention in these patients and persistent cognitive side effects are minimal.